“Unbroken, but Bent”: Gendered Racism in School Leadership - Burton, Laura J.; Cyr, Daron; Weiner, Jennie Miles (Frontiers in Education, 2020)
Black women experience the burdens of gendered racism in their roles as school leaders, yet little is known about how these leaders cope with those experiences or how such coping might impact their ability or desire, to persist and thrive in such positions. This phenomenological study examined the experiences of 10 Black female school leaders and how they coped with gendered racism and the costs associated with doing so. Findings show coping occurred through both adaptive and maladaptive strategies, which we label as “more affirming” or “less affirming”, to highlight how both enabled participants to persist in their leadership roles. More affirming (i.e., adaptive) strategies included reliance on faith, social relationships and professional networks, and advocacy roles to confront, manage, and problem solve around their experiences of gendered racism. Less affirming (i.e., maladaptive) strategies included denial or avoidance, buffering and boundary setting, and in a few cases, exit. Further, findings revealed the costs or tolls borne by participants included internalizing gendered racism, doubting leadership skills and competence, anger at having to operate in a gendered racist context, and resignation. By acknowledging and naming the gendered racism Black female school leaders face and the energy required to exert to cope with it, these findings highlight the need to discuss gendered racism in educational leadership and professional development programs. Further, these findings suggest anti-racist practices by White allies, including shifting the burden of gendered racism to them, is critical to the disruption of practices privileging Whiteness in educational leadership.